Deteksi Puncak Amplitudo dan Durasi Gelombang QRS Elektrokardiogram Menggunakan Discrete Data - Setiawidayat Sabar; Aviv Yuniar Rahman; Ratna Hidayati (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
In each cycle of the Heart on the Electrocardiogram there are generally P waves as a presentation of Atrial Muscle Depolarization, QRS waves as a presentation of Ventricular Muscle Depolarization and T waves as a presentation of Ventricular Muscle Repolarization. Some types of electrocardiographs only represent wave morphology and some other types of electrocardiographs are equipped with duration and amplitude information but are limited. This limitation of information is calculated manually using small boxes on ecg paper measuring 40 ms for duration and 1 mV for amplitude. The consequences of this manual calculation will require time and accuracy of the calculation results. This study aims to obtain the QRS wave duration along with the amplitude value in each cycle of cardiac examination results. Discrete data from the sampling results of the ECG continuous signal in the maximum filter amplitude to get peak R values. The position of integer peak R with the next peak R is the duration of the cycle. PQRST algorithm is used to obtain peak Q and peak S, so the duration of QS can be obtained by subtracting the position of integer peak S with integer position Q. 10 samples of discrete ecg Sinus Rhythm data from Physionet and 5 samples from ECG-UWG were used in this study. The results showed that all sample data in 3 cycles had a value of QRS duration and peak amplitude values ​​Q, R and S. Peak amplitude R max values ​​and R min physionet sample records were obtained in record 16273 which was 3,485 mV and record 16795 was 0.805 mV. The QRS duration for Bradicardia and Tachicardia is shown in record 16483 which is 40 ms and record 17052 which is 144 ms.